A preload cooperative sensing scheme with low overhead in cognitive radio networks. Issue 9 (27th May 2015) - Liu, Lizheng; Liu, Fangai; Yang, Lu; Liu, Jian; Zhang, Zhizhong
Abstract: In cognitive radio networks (CRNs), users can collaborate to improve the accuracy of spectrum sensing, but a large number of secondary users reporting their local sensing results may create significant overhead. In this paper, we propose a new pre‐sensing scheme, called preload cooperative sensing (PCS), which not only attains the given sensing accuracy for CRNs but also reduces the whole sensing time T . In order to reduce the sensing overhead in CRNs, the proposed scheme adopts two key technologies: selective reporting technology and pre‐sensing sequential detection technology. Selective reporting technology implies that only those users, which detect the presence of primary users, need to report the results, while pre‐sensing sequential detection technology is an asynchronous parallel scheme, which sets a threshold to determine the presence of primary users. Considering the preload sensing slots, we derive a formula to express the overall miss detection probability, and at a given Quality of Service (QoS) value, the sensing overheads of PCS are analyzed over Rayleigh fading channel. Also, we consider the overhead minimization problems in PCS. Simulation results show the superiority and efficiency of the PCS scheme. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this paper, we propose a new pre‐sensing scheme, called preload cooperative sensing (PCS), which not only attains the given sensing accuracy for CRNs but also reduces the whole sensing time T . The proposed scheme adopts two key technologies: selective reporting technology and pre‐sensing sequential detection technology. Considering the preload sensing slots, we derive a formula to express the overall miss detection probability, and at a given QoS value, the sensing overheads of PCS are analyzed over Rayleigh fading channel.